2010
DOI: 10.1590/s1806-37132010000400003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e gravidade da sibilância no primeiro ano de vida

Abstract: Objective: To determine the prevalence and severity of wheezing in infants, using the standardized protocol devised for the "Estudio Internacional de Sibilancias en Lactantes" (EISL, International Study of Wheezing in Infants), as well as to determine the relationship between such wheezing and physician-diagnosed asthma, in the first year of life. Methods: Between March of 2005 and August of 2006, the EISL questionnaire was administered to the parents or legal guardians of infants undergoing routine procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
23

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 21 publications
4
20
0
23
Order By: Relevance
“…In this research it was observed that there was a predominance of male infants whistling as has been shown by several researchers [5][6][7][8][9][10] , but cal-culated the prevalence ratio was not significant. The reason for this gender difference is based on lower airway caliber male relative to the female gender 13 , this relationship, which is reversed as the child reaches adolescence.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In this research it was observed that there was a predominance of male infants whistling as has been shown by several researchers [5][6][7][8][9][10] , but cal-culated the prevalence ratio was not significant. The reason for this gender difference is based on lower airway caliber male relative to the female gender 13 , this relationship, which is reversed as the child reaches adolescence.…”
Section: Discussionmentioning
confidence: 49%
“…Infants who have a family history of asthma 2,6,15 ,rhinitis 15 and allergic dermatitis have the greatest chance to present episodes of wheezing in the first 12 months of life, showing that heredity is an important risk factor for wheezing and asthma later 2,5,6,10,12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Verificaram-se reinternação da criança pelo mesmo episódio em 2,1% dos casos e reinternação da mesma criança por outro episódio em 24,8% A idade mostrou-se inversamente relacionada à prevalência de sibilância nas crianças Guarani. A precocidade na apresentação de sibilân-cia em crianças foi descrita por diversos autores em populações carentes atendidas em serviços públicos de saúde em cidades do Sul e Sudeste do Brasil 2,20,21 . Em estudo em pacientes atendidos em unidades básicas de saúde em São Paulo, encontrou-se uma prevalência elevada de sibilância, com quase metade dos lactentes apresentando pelo menos um episódio de sibilância já no primeiro ano de vida 2 .…”
Section: Resultsunclassified
“…A morbimortalidade por causas respiratórias relacionadas à sibilância é elevada, sendo mais vulneráveis os lactentes de populações socieconomicamente menos favorecidas 2 , nos quais o primeiro episódio de sibilância pode resultar de inflamação dos bronquíolos de etiologia viral, a bronquiolite viral aguda 3 . Na América Latina, a sibilância em lactentes tem sido frequentemente relacionada à exposição precoce e continuada a agentes inalantes do ambiente e às infecções respiratórias virais, podendo evoluir com complicações, como a pneumonia 4 .…”
Section: Introductionunclassified